The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.tube.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect size of type 2 diabetes mellitus on tuberculosis drug resistance and adverse treatment outcomes

Abstract: 2 AbstractObjective: To evaluate the effect size of type 2 diabetes mellitus (T2DM) on tuberculosis (TB) treatment outcomes and multi drug resistance (MDR). Methods:A cohort with 507 individuals with diagnosed TB included 183 with coexistence of T2DM and TB (TB-T2DM). Participants were identified at the time of TB diagnosis and followed during the course of TB treatment. Then we computed relative risks and adjustments by Cox proportional hazards for outcome variables (drug resistance, death, relapse, treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 36 publications
3
38
0
Order By: Relevance
“…Patients with diabetes–TB co‐infection are more likely to remain positive after initial antitubercular treatment, and to exhibit higher resistance to frontline drugs. Moreover, these people are more likely to have multidrug‐resistant TB, treatment failure, and relapse, as reported in another study from Mexico …”
supporting
confidence: 58%
“…Patients with diabetes–TB co‐infection are more likely to remain positive after initial antitubercular treatment, and to exhibit higher resistance to frontline drugs. Moreover, these people are more likely to have multidrug‐resistant TB, treatment failure, and relapse, as reported in another study from Mexico …”
supporting
confidence: 58%
“…Since 2010, several large cohort studies reported unfavourable effects of DM on TB outcomes. DM was associated with more severe clinical manifestations of TB such as higher frequency of cavities on chest X‐ray and higher hospitalization rates . Patients with DM were more likely to have up to 2 times higher TB reactivation, recurrence, and relapse .…”
Section: Introductionmentioning
confidence: 95%
“…DM was associated with more severe clinical manifestations of TB such as higher frequency of cavities on chest X‐ray and higher hospitalization rates . Patients with DM were more likely to have up to 2 times higher TB reactivation, recurrence, and relapse . TB‐DM patients were more likely to have delayed sputum conversion and higher probability of treatment failure .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Diabetes predisposes to tuberculosis due to the profound effects of hyperglycemia on body defense mechanisms including suppression of cell-mediated immune mechanisms [10]. It is also well known that presence of diabetes mellitus also alters the way pulmonary tuberculosis manifests and adversely affects clinical and treatment outcomes [11]. It also results in slow conversion to a sputum-negative state [12].…”
mentioning
confidence: 99%